Two new species of Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from southern India - Sayyed, Amit; Kirubankaran, Samson; Khot, Rahul; Harsan, Shiva; Adhikari, Omkar; Sayyed, Ayaan; Sayyed, Masum; Fazil, Ahamed; Jerith, Ahamed; Deshpande, Shubhankar; Purkayastha, Jayaditya; Sulakhe, Shauri (Zootaxa, 2023)
We describe two new species of Cnemaspis from Alagarkovil, Madurai District and Mekkarai, Shenkottai, Tenkasi, southern India, based on molecular and morphological data. The new species differ from their congeners by genetic divergences of 4.8–16.1% and 14.8–31.6% for the ND2 mitochondrial gene. Two new species belong to the Cnemaspis gracilis and Cnemaspis beddomei clades, respectively. Molecular data for the newly described Cnemaspis aaronbaueri from its type locality is also presented, and its phylogenetic position is established.